The Role of Virtual Communities on Consumer Purchase Decisions with Brand Equity as Mediating Variable - St. Rukaiyah (Manunggal Halim Jaya, 2022)
This study aims to analyze the relationship between virtual communities variabel on consumer purchase decision with brand equity as mediating vaiable. The sample in this study was selected with the 100 respondent with Snowball sampling and data colletion with survey. This study uses the PLS method. Next is a hypothesis to test whether there is a relationship between virtual communities, brand equity, and purchasing decisions at PT. Hadji Kalla Toyota Makassar. The analytical tool used in this research is Partial Least Square (PLS). Research using WarpPLS 6.0 program. The result of this study state Virtual communities are established to significantly affect purchasing decisions; Virtual communities are proven to have a significant positive effect on brand equity; The Virtual Communities variable shows a solid and dominant influence on brand equity compared to other variables; This study has provided findings on the effect of Virtual Communities on purchasing decisions through brand equity. Virtual Communities will have a role in delivering information that can produce word of mouth and become a choice for prospective buyers to see reviews and the advantages of products. That can be a consideration for companies in developing their marketing strategies, especially in building customer loyalty to the brand.